Faktor Psikologis yang Mempengaruhi Maharah Kalam Mahasiswa Pendidikan Bahasa Arab UIN SU Medan - Tria Wulandari; Regina Valda Garzita; Sahkholid Nasution (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2025)
This study aims to explore the psychological factors that affect speaking ability in Arabic among Arabic Language Education students at UIN Sumatera Utara (UIN SU). Dominant psychological factors include language anxiety, motivation, self-efficacy, and self-confidence. Language anxiety serves as a major barrier to speaking due to fear of negative judgment. Meanwhile, high intrinsic and extrinsic motivation plays a significant role in encouraging students to be more active in practicing. High self-efficacy helps students feel more confident in their abilities even when making mistakes, while strong self-confidence provides encouragement to not fear making errors. The research method used is a descriptive qualitative approach, involving in-depth interviews, classroom observations, and literature analysis. The results of the study indicate that language anxiety hinders students' speaking ability, while high motivation and self-efficacy enhance their self-confidence and speaking skills. This study suggests the importance of applying teaching strategies that consider psychological factors and create a supportive environment to improve Arabic speaking skills among students.